(untitled) (Razi Medical Journal, 2025)
Presence of Bacterial contamination in hospital environments, particularly intensive care units, poses a serious threat to global public health in the world with high morbidity and mortality rates. Of more concern is the emergence of multidrug-resistant bacteria on medical devices, inanimate surfaces, health care providers, and patients in the intensive care unit, which could lead to further cross-contamination and infection. This study aimed to assess the bacterial profile and their antimicrobial susceptibility patterns of bacterial isolates from the intensive care unit of the Emergency unit, internal medicine, and coronary unit of Misurata Central Unit of Misurata, Libya. A unit-based cross-sectional study was conducted on three Intensive Care units from 1st December 2024 to 27th December 2024. In this project, a total of 102 swab samples from the intensive care unit environment were collected using cotton swabs. Standard Microbiological techniques to include culture method and Gram stain, were employed for the identification of the isolates. Antimicrobial susceptibility tests for bacterial isolates were performed by using the Kirby-Bauer disk diffusion method. In the total of 102 swab samples, bacterial growth was observed in 19.6% (20/102) of the total samples. Out of the total bacterial growth recovered, the Coronary care unit had the highest, 50% (10/20), followed by the Emergency unit 35% (7/20), and the Internal medicine unit had 15% (3/20). The most frequently found isolate was Staphylococcus aureus 75% (15/20), followed by Streptococcus pyogenes 15% (3/20), Pseudomonas aeruginosa 5% (1/20), and E coli 5% (1/20). Results of the antibiotic susceptibility pattern revealed that most of the isolates are multidrug-resistant. Results from this study showed bacterial contamination of the ICU environments and their resistance patterns, which suggest that patients are prone to hospital-associated infection. It is recommended that strict sterilization of intensive care units be standardized and the hygiene of hospital workers be enforced to prevent transmission of infection in hospital environments.